О причинах декомпенсации гипертрофированного сердца - Д. С. Саркисов (Հայկական ՍՍՀ գիտությունների ակադեմիա)
Հեղինակը ցույց է տալիս, որ գերաճած սրտի դեկոմպենսացիայի վերաբերյալ զանազան տեսությունների հիմքում ընկած են սրտամկանի բջիջի նյութական միջոցների սպառումը։ The author shows that the different theories on the origin of hypertrophic heart decomensation are based upon the notion of exhaustion of material resources of myocardial cells.
Keywords: Physiology; Medicine; Science; Pathology